Anti-money laundering and counter-terrorist financing in the Luxembourg investment fund market - Andrea Dietz (European Institute for Knowledge & Value Management (EIKV), 2017)
The field of Anti-Money Laundering and Counter-Terrorist Financing in their current form have had an important impact on the financial world for almost half a century. Today, Money Laundering and Terrorist Financing pose a threat to the integrity of the financial markets and systems worldwide. The intention behind implementing a regulatory Anti-Money Laundering and Counter-Terrorist Financing framework is to cut off the financial resources of criminals and to follow back the traces that financial transactions leave to the backers of the criminal organizations. Luxembourg, being the second largest center for investment funds in the world and the leading one in Europe, is dependent on its good reputation, a cornerstone of its success. Based on this, the risk exposure of the Luxembourg Fund Market with respect to Money Laundering and Terrorist Financing shall be assessed and a risk assessment for an investment fund established. Firstly, a general introduction to Money Laundering and Terrorist Financing is provided, which is complemented by a chapter specifying details of each criminal offence, differences and similarities, and the threats and harms both crimes pose. Secondly, the legal definitions and local obligations of the market participants are presented. Thirdly, the Luxembourg Fund Market in terms of figures, products and its participants in investment fund structure are addressed. In a next step, the summary of three expert interviews is presented. The questions asked are based on the information, statements and findings in the previous chapters. All information obtained is then used to establish a general risk assessment of an investment fund and to draw the final conclusion. The results show that the inherent risk of the Luxembourg Fund Market is concentrated on Money Laundering rather than on Terrorist Financing. The residual risk is completely dependent on the measures implemented by the single structures and therefore cannot really be quantified. It is very much dependent on the risk appetite of the market participants, their controls in place and the enforcement of the rules, especially when it comes to cross-border business.
Keywords: 330